The Initiation of Safety-Enhancing Actions in Railway Crossings Using Modelling Procedures - Szabó, L.; Somogyi, M.; Horváth, G. (Acta Technica Jaurinensis, 2015)
Thisstudy is examining the application opportunities of models, and it is revealinga possible solution which can be the basis of creating a catalogue which canestablish the reconstruction of railway crossings. This reconstruction catalogue is suggestinginfrastructure changes and new traffic management procedures with takingaccount of the controlled model outputs. Based on the reconstruction catalogue,feasibility studies and construction project documentations can be made.papercontains the description of the prescribed format of the papers published inthe periodical entitled “Acta Technica Jaurinensis”. The length of the abstractis between 500-1000 characters including spaces. Avoid using references in theabstract.